Local versus general anaesthesia for carotid endarterectomy - Tanat Vaniyapong (2018)
© 2013 The Cochrane Collaboration. Background: Carotid endarterectomy may significantly reduce the risk of stroke in people with recently symptomatic, severe carotid artery stenosis. However, there are significant perioperative risks that may be reduced by performing the operation under local rather than general anaesthetic. This is an update of a Cochrane Review first published in 1996, and previously updated in 2004 and 2008. Objectives: To determine whether carotid endarterectomy under local anaesthetic: (1) reduces the risk of perioperative stroke and death compared with general anaesthetic; (2) reduces the complication rate (other than stroke) following carotid endarterectomy; and (3) is acceptable to patients and surgeons. Search methods: We searched the Cochrane Stroke Group Trials Register (September 2013), MEDLINE (1966 to September 2013), EMBASE (1980 to September 2013) and Index to Scientific and Technical Proceedings (ISTP) (1980 to September 2013). We also handsearched relevant journals, and searched the reference lists of articles identified. Selection criteria: Randomised trials comparing the use of local anaesthetic to general anaesthetic for carotid endarterectomy were considered for inclusion. Data collection and analysis: Three review authors independently assessed trial quality and extracted data. We calculated a pooled Peto odds ratio (OR) and corresponding 95% confidence interval (CI) for the following outcomes that occurred within 30 days of surgery: stroke, death, stroke or death, myocardial infarction, local haemorrhage, cranial nerve injuries, and shunted arteries. Main results: We included 14 randomised trials involving 4596 operations, of which 3526 were from the single largest trial (GALA). In general, reporting of methodology in the included studies was poor. All studies were unable to blind patients and surgical teams to randomised treatment allocation and for most studies the blinding of outcome assessors was unclear. There was no statistically significant difference in the incidence of stroke within 30 days of surgery between the local anaesthesia group and the general anaesthesia group. The incidence of strokes in the local anaesthesia group was 3.2% compared to 3.5% in the general anaesthesia group (Peto OR 0.92, 95% CI 0.67 to 1.28). There was no statistically significant difference in the proportion of patients who had a stroke or died within 30 days of surgery. In the local anaesthesia group 3.6% of patients had a stroke or died compared to 4.2% of patients in the general anaesthesia group (Peto OR 0.85, 95% CI 0.63 to 1.16). There was a non-significant trend towards lower operative mortality with local anaesthetic. In the local anaesthesia group 0.9% of patients died within 30 days of surgery compared to 1.5% of patients in the general anaesthesia group (Peto OR 0.62, 95% CI 0.36 to 1.07). However, neither the GALA trial or the pooled analysis were adequately powered to reliably detect an effect on mortality. Authors' conclusions: The proportion of patients who had a stroke or died within 30 days of surgery did not differ significantly between the two types of anaesthetic techniques used during carotid endarterectomy. This systematic review provides evidence to suggest that patients and surgeons can choose either anaesthetic technique, depending on the clinical situation and their own preferences.